(untitled) (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Prasetyo EN, Permanasari Y, Basyirah A, Fitriya SA, Jadid N, Zulaikah S, Ekawati I, Isdiantoni, Koentjoro MP. 2024. Aquaculture infection of Kappaphycus alvarezii by Vibrio alginolyticus causing ice-ice disease. Biodiversitas 25: 4086-4094. The occurrence of ice-ice disease on seaweed (Kappaphycus alvarezii (Doty) Doty ex P.C.Silva) tissue is indicated by the presence of bleaching and softening symptoms on thallus, which attracts microbial infection. In addition, it is often caused by unfavorable environmental conditions during specific seasons and is characterized by fragmentation as well as a reduction in biomass. To prevent the disease, several studies have suggested the use of ice-ice disease-resistant seeds. Therefore, the aim of this study was to investigate the resistance level of seaweed seeds to microbial infection, particularly Vibrio alginolyticus, which is responsible for ice-ice disease in different aquaculture areas in Sumenep District. Data were collected from four different villages, including Brakas, Padike, Tanjung, and Lobuk, followed by analysis using descriptive qualitative method. K. alvarezii seeds collected from four villages were infected with V. alginolyticus using the in vitro method. Thallus of seaweed was then observed and water samples were taken every 6 hours for 24 hours post-infection. The results showed that seeds from Brakas had the lowest (11%) infection rate, followed by Tanjung (67%), and Padike and Lobuk (89% each). This indicated that K. alvarezii seeds from Brakas possessed a prominent activity against V. alginolyticus infection with no sign of chlorosis or tissue softening on thallus.